Microwave vs. solvothermal synthesis of hollow cobalt sulfide nanoprisms for electrocatalytic hydrogen evolution and supercapacitors1. Issue 20 (11th March 2015) - You, Bo; Jiang, Nan; Sheng, Meili; Sun, Yujie
<x xml:space="preserve">Abstract</x> Hollow cobalt sulfide nanoprisms obtained by a two-step, microwave-assisted synthesis within 15 min exhibit higher hydrogen evolution catalytic activity and better specific capacitance than its counterpart prepared by a traditional solvothermal method.